Effect of Integration of Organic and Inorganic Sources of Nitrogen on Growth, Yield and Nutrient Uptake by Maize (Zea mays L.) - Kafle, Sagar; Sharma, P. K. (International Journal of Applied Sciences and Biotechnology, 2015)
A field study was conducted at Agronomy Research Farm of Punjab Agricultural University during kharif 2013 to evaluate the effect of organicand inorganic sources of nitrogen on maize. Experiment was laid out in split plot design with four replications comprising three farmyardmanure levels (0, 15 and 20 t/ha) in main-plots and five nitrogen levels 0, 75, 100, 125 and 150% of recommended dose (125 kg/ha) throughinorganic fertilizer in sub-plots. Plant growth and yield characters and nutrient content as well as uptake were recorded. Number of leaves, leafarea index, chlorophyll content and leaf nitrogen content at periodic intervals increased significantly with the application of farmyard manureand nitrogen. Increase in nutrient uptake viz., nitrogen, phosphorus and potassium uptake along with micronutrient uptake by grain was alsoobserved with incremental farmyard manure and nitrogen levels. Growth variables were correlated positively with each other and with grainyield. A fairly negative correlation was observed between micronutrient content and growth and yield variables. DOI: http://dx.doi.org/10.3126/ijasbt.v3i1.11849 Int J Appl Sci Biotechnol, Vol. 3(1): 31-37